Is Peer Interaction Necessary for Optimal Active Learning? Using Minimal Pairs for Improved Students’ Pronunciation Ability - Kholid, M. Ridho; Haryanto P, Fika Indhiswari (English Education: Jurnal Tadris Bahasa Inggris, 2017)
In teaching and learning process in the class, there are a lot of students who find some difficulties in learning English. One of the difficulties that the students find in English learning activity is pronunciation. Pronunciation is important because it is the way someone communicate to other, express ideas, feelings, and thought in speaking form. The objective of this research is to know whether there is an Influence of Using Minimal Pairs towards Students’ Pronunciation Ability. The research methodology used was quasi experimental design. In this study, we analyzed student responses on an optimized pretest and posttest administered during two different class in a english course. The researcher took two classes, one class as the experimental class and one class as the control class. In the experimental class, the researcher used Minimal Pairs and in the control class the teacher used Reading Aloud. The meetings held in three times in which 2 x 45 minutes for each class. After doing posttest, then the researcher analyzed the data using SPSS to compute t . The result is using Minimal Pairs was a significant influence towards students’ pronunciation ability. It shown from Sig = 0.025 < ? = 0.05.